Intensive Olfactory Training in Post-COVID Patients: A Randomized Multicenter Clinical Trial - Pires, Ícaro Almeida Toledo (2022)
Introduction: Olfactory dysfunction (OD) is one of the most reported symptoms of COVID -19. Previous studies have identified olfactory training (OT) as an important treatment for postinfectious OD, but little is known about its effect after SARS-CoV-2 infection and how it can be optimized. Objective: To assess whether OT can be optimized if performed intensively, with more fragrances over a shorter period in patients with persistent OD after COVID -19. Also, to determine the presence of other variables related to OD and treatment response in this population. Method: This multicenter randomized clinical trial recruited 80 patients with persistent OD with previous COVID-19 for less than three months. The patients were divided into two groups, who received treatment with 4 and 8 essences over four weeks. Subjective assessments and the University of Pennsylvania Smell Identification Test (UPSIT) were performed before and after treatment. Results: A significant improvement in olfaction was measured subjectively and on UPSIT in both groups, but without significant differences between groups. In addition, the presence of olfactory fluctuation was associated with higher UPSIT scores. Conclusion: These data suggest that intensifying the training by increasing the number of essences for 4 weeks does not show superiority over the classical method. Moreover, a fluctuating olfactory ability seems to be related to a better score in the UPSIT.